Selected Lectures of the 3rd Course of Perinatal and Pediatric Cardiology; Cagliari (Italy); October 23, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the 3rd Course of Perinatal and Pediatric Cardiology; Cagliari (Italy); October 23, 2024   The 3rd Course of Perinatal and Pediatric Cardiology is a Satellite Meeting of the 20th International Workshop on Neonatology and Pediatrics, Cagliari (Italy), October 23rd-26th, 2024.   LECT 1. PRENATAL DIAGNOSIS OF CONGENITAL HEART DISEASES: HOW AND WHERE TO GIVE BIRTH? • P. Neroni, A. Atzei (Cagliari, Italy) LECT 2. CARDIOVASCULAR HEALTH AND EXERCISE IN CHILDREN WITH CONGENITAL HEART DISEASES • F. De Luca (Catania, Italy) LECT 3. HEART AND MIND: THE HIDDEN LINK • G. Concas, E. Esposito, A. Atzei, P. Neroni (Cagliari, Italy) LECT 4. INTERCURRENT PATHOLOGIES, CONGENITAL HEART DISEASES AND CLINICAL MANAGEMENT: WHAT ELSE? • A. Atzei, G. Concas, C. Trenta, R. Pintus, P. Neroni (Cagliari, Italy) LECT 5. ARTERIAL HYPERTENSION IN THE CHILD • P.P. Bassareo (Dublin, Ireland) LECT 6. CONGENITAL HEART DISEASE: HOW TO MANAGE THE TRANSITION FROM CHILDHOOD TO ADULTHOOD • M. Chessa, S. Flocco, A. Magon (Milan, Italy) LECT 7. SPORTS CERTIFICATION: DIFFERENCES BETWEEN ITALY AND OTHER COUNTRIES • R. Solinas (Cagliari, Italy) LECT 8. METABOLOMICS AND PEDIATRIC CARDIOLOGY • R. Pintus (Cagliari, Italy)